Borna disease virus infection in racing horses with behavioral and movement disorders - Berg, Anna-Lena; Dörries, Rüdiger; Berg, Mikael (Archives of virology, 1999)
Borna disease virus (BDV) is a neurotropic agent with capacity to infect and cause neurological disease in a broad range of warmblooded hosts including horses, sheep, cattle, cats, and possibly also humans. The epidemiology of BDV is largely unknown. However, it is likely that subclinically infected animals may represent potential virus reservoirs. In two groups of Swedish racing horses, one clinically healthy and one consisting of horses with diffuse neurological signs, the BDV seroprevalence was 24.5% and 57.7%, respectively. BDV RNA was detected in peripheral blood mononuclear cells in 8 out of 28 (28.6%) investigated horses, the majority of the BDV RNA-positive horses belonging to the group with neurological signs. There was a close relationship between the Swedish equine BDV isolates and previously reported equine BDVs in Europe. Our results point to an association of BDV infection with atypical disease patterns in horses such as diffuse mental and gait disturbances. These findings may be of importance for the understanding of the epidemiology of BDV infections in animals and man.